Containing the Threat from Illegal Bombings: An Integrated National Strategy for Marking, Tagging, Rendering Inert, and Licensing Explosives and Their Precursors - National Research Council (The National Academies Press, 1998)
In response to the rising concern of the American public over illegal bombings, the Bureau of Alcohol, Tobacco, and Firearms asked the National Research Council to examine possible mechanisms for reducing this threat. The committee examined four approaches to reducing the bombing threat: addition of detection markers to explosives for pre-blast detection, addition of identification taggants to explosives for post-blast identification of bombers, possible means to render common explosive materials inert, and placing controls on explosives and their precursors. The book makes several recommendations to reduce the number of criminal bombings in this country.
Keywords: Conflict and Security Issues

Marking, Rendering Inert, and Licensing of Explosive Materials: Interim Report - National Research Council (The National Academies Press, 1997)
Keywords: Conflict and Security Issues

Implementing Health-Protective Features and Practices in Buildings: Workshop Proceedings: Federal Facilities Council Technical Report #148 - National Research Council (The National Academies Press, 2005)
Indoor environmental quality (IEQ) is influenced by building design; heating, ventilation, and air-conditioning systems; and construction materials, as well as by building operations, maintenance, and housekeeping procedures. Increasing evidence suggests that adverse health outcomes in employees, students, hospital patients, and others are linked to the presence of indoor pollutants and other aspects of poor-quality indoor environments. Implementing Health-Protective Features and Practices in Buildings explores this issue and discusses ongoing research and possible strategies for implementing changes in standards and practices for indoor environmental quality.
Keywords: Engineering and Technology; Health and Medicine

Black and Smokeless Powders: Technologies for Finding Bombs and the Bomb Makers - National Research Council (The National Academies Press, 1998)
Some 600 pipe bomb explosions have occurred annually in the United States during the past several years. How can technology help protect the public from these homemade devices? This book, a response to a Congressional mandate, focuses on ways to improve public safety by preventing bombings involving smokeless or black powders and apprehending the makers of the explosive devices. It examines technologies used for detection of explosive devices before they explode—including the possible addition of marking agents to the powders—and technologies used in criminal investigations for identification of these powders—including the possible addition of taggants to the powders—in the context of current technical capabilities. The book offers general conclusions and recommendations about the detection of devices containing smokeless and black powders and the feasibility of identifying makers of the devices from recovered powder or residue. It also makes specific recommendations about marking and tagging technologies. This volume follows the work reported in Containing the Threat from Illegal Bombings (NRC 1998), which studied similar issues for bombings that utilize high explosives.
Keywords: Conflict and Security Issues

Protecting People and Buildings from Terrorism: Technology Transfer for Blast-effects Mitigation - National Research Council (The National Academies Press, 2001)
Concerned with the vulnerability of U.S. civilian and military personnel to terrorist bombing attacks, the U.S. Congress directed the Department of Defense to undertake a comprehensive research and testing program aimed at protecting people in buildings from such attacks. The Blast Mitigation for Structures Program (BMSP) was initiated in 1997 and has produced a large volume of experimental and analytical data that will permit the design of new, more robust buildings as well as the development of methods to retrofit a large number of vulnerable existing structures. This report reviews the BMSP program and investigates a process that would use existing institutional infrastructures (i.e., building code and standards-writing organizations, professional and technical organizations, universities, and research centers) to disseminate knowledge.
Keywords: Conflict and Security Issues; Engineering and Technology

Blast Mitigation for Structures: 1999 Status Report on the DTRA/TSWG Program - National Research Council (The National Academies Press, 2000)
The Blast Mitigation for Structures Program (BMSP) is a research and development activity conducted by the Defense Threat Reduction Agency (DTRA) to improve the performance of buildings that are targets of terrorist attack. The primary goal of the BMSP is to reduce loss of life and injuries to the occupants of these buildings through the development of innovative techniques for new structures and retrofitting existing facilities. The committee's findings and recommendations are contained in this initial assessment report.
Keywords: Engineering and Technology; Conflict and Security Issues

Nanotechnology for the Intelligence Community (The National Academies Press, 2005)
The emergence of nanotechnology as a major science and technology research topic has sparked substantial interest by the intelligence community. In particular the community is interested both in the potential for nanotechnology to assist intelligence operations and threats it could create. To explore these questions, the Intelligence Technology Innovation Center asked the National Research Council to conduct a number of activities to illustrate the potential for nanotechnology to address key intelligence community needs. In 2004, workshop reports were issued on power systems and on positioning and sensing technologies. The final report provides an assessment of a wide range of additional technologies. The report also presents a series of findings and recommendations about areas of opportunities for the intelligence community and strategies for exploiting these opportunities.
Keywords: Conflict and Security Issues

Improving Risk Communication - National Research Council (The National Academies Press, 1989)
Technological risk and the process of explaining risks to the public have become major public issues. The mention of Bhopal or Love Canal can provoke emotional arguments—not only about the hazards themselves but also about how they were explained to the public. As new laws, the threat of AIDS, and other factors make risk communication more crucial, officials in government and industry are seeking guidelines on how to communicate effectively and responsibly. This volume offers an approach to better quality in risk communication. The combined insight of experts from government, business, and universities, Improving Risk Communication draws on the most current academic and practical information and analysis. Issues addressed include why risk communication has become more difficult in recent decades, what the major problems are, and how common misconceptions often hamper communication campaigns. Aimed especially at top decisionmakers in government and industry, the book emphasizes that solving the problems of risk communication is as much about improving procedures as improving the content of risk messages. Specific recommendations for change include a Risk Message Checklist and a call for developing a consumer's guide to risk. Appendixes provide additional details.
Keywords: Computers and Information Technology

An Assessment of the National Institute of Standards and Technology Manufacturing Engineering Laboratory: Fiscal Year 2008 - National Research Council (The National Academies Press, 2008)
The mission of the Manufacturing Engineering Laboratory (MEL) of the National Institute of Standards and Technology (NIST) is to promote innovation and the competitiveness of U.S. manufacturing through measurement science, measurement services, and critical technical contributions to standards. The MEL is organized in five divisions: Intelligent Systems, Manufacturing Metrology, Manufacturing Systems Integration, Precision Engineering, and Fabrication Technology. A panel of experts appointed by the National Research Council (NRC) assessed the first four divisions. Overall, this book finds that the four individual divisions are performing to the best of their ability, given available resources. In many areas in all four divisions, the capabilities and the work being performed are among the best in the field. However, reduced funding and other factors such as difficulty in hiring permanent staff are limiting (and are likely to increasingly limit) the degree to which MEL programs can achieve their objectives and are threatening the future impact of these programs.
Keywords: Engineering and Technology

Airline Passenger Security Screening: New Technologies and Implementation Issues - National Research Council (The National Academies Press, 1996)
This book addresses new technologies being considered by the Federal Aviation Administration (FAA) for screening airport passengers for concealed weapons and explosives. The FAA is supporting the development of promising new technologies that can reveal the presence not only of metal-based weapons as with current screening technologies, but also detect plastic explosives and other non-metallic threat materials and objects, and is concerned that these new technologies may not be appropriate for use in airports for other than technical reasons. This book presents discussion of the health, legal, and public acceptance issues that are likely to be raised regarding implementation of improvements in the current electromagnetic screening technologies, implementation of screening systems that detect traces of explosive materials on passengers, and implementation of systems that generate images of passengers beneath their clothes for analysis by human screeners.
Keywords: Transportation and Infrastructure; Conflict and Security Issues

Globalization of Defense Materials and Manufacturing: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Emerging economies, social and political transitions, and new ways of doing business are changing the world dramatically. To be the leader in this competitive climate, a defense manufacturing enterprise will require up-to-date capabilities, which include improvements in materials processing, among other things. Also, national and international efforts to mitigate environmentally harmful effects of industrial processes and to improve decision making for handling and disposing of industrial contaminants adds additional requirements for any future efforts. The objective of retaining high-value materials-related manufacturing as a key national competitive capability implies a number of factors. The value of specific manufacturing capabilities could be defined not only in terms of criticality to defense systems but also in relation to technology and knowledge content, importance as a supplier to other industries, and importance to U.S. exports.
Keywords: Engineering and Technology; Conflict and Security Issues

Summary of the Sensing and Positioning Technology Workshop of the Committee on Nanotechnology for the Intelligence Community: Interim Report - National Research Council (The National Academies Press, 2004)
The emergence of nanotechnology as a major science and technology research topic has sparked substantial interest by the intelligence community. In particular the community is interested both in the potential for nanotechnology to assist intelligence operations and threats it could create. To explore these questions, the Intelligence Technology Innovation Center asked the National Research Council to conduct a number of activities to illustrate the potential for nanotechnology to address key intelligence community needs. The second of these was a workshop to explore how nanotechnology might enable advances in sensing and locating technology. This report presents a summary of that workshop. In includes an overview of security technologies, and discussions of systems, natural chemical/biological tags, passive chemical/biological tags, and radio/radar/optical tags.
Keywords: Engineering and Technology; Health and Medicine

Summary of the Power Systems Workshop on Nanotechnology for the Intelligence Community: Interim Report - National Research Council (The National Academies Press, 2004)
The emergence of nanotechnology as a major science and technology research topic has sparked substantial interest by the intelligence community. In particular the community is interested both in the potential for nanotechnology to assist intelligence operations and threats it could create. To explore these questions, the Intelligence Technology Innovation Center asked the National Research Council to conduct a number of activities to illustrate the potential for nanotechnology to address key intelligence community needs. The first of these was a workshop to explore technology opportunities and challenges in power systems that could be addressed by nanotechnology. This report presents a summary of that workshop. It includes an overview of power technologies and discussions on nanoscale properties of energy storage materials, device experience, manufacturing and material handling considerations, and natural power.
Keywords: Conflict and Security Issues; Industry and Labor

An Assessment of the National Institute of Standards and Technology Manufacturing Engineering Laboratory: Fiscal Year 2010 - National Research Council (The National Academies Press, 2010)
The mission of the Manufacturing Engineering Laboratory (MEL) of the National Institute of Standards and Technology (NIST) is to promote innovation and the competitiveness of U.S. manufacturing through measurement science, measurement services, and critical technical contributions to standards. The MEL is organized in five divisions: Intelligent Systems, Manufacturing Metrology, Manufacturing Systems Integration, Precision Engineering, and Fabrication Technology. A panel of experts appointed by the National Research Council (NRC) assessed the first four divisions.
Keywords: Engineering and Technology

Biomolecular Self-Assembling Materials: Scientific and Technological Frontiers - National Research Council (The National Academies Press, 1996)
Keywords: Engineering and Technology; Biology and Life Sciences

Government/Industry Forum on Capital Facilities and Core Competencies: Summary Report - National Research Council (The National Academies Press, 1998)
Keywords: Engineering and Technology

Future Biotechnology Research on the International Space Station - National Research Council (The National Academies Press, 2000)
Under current NASA plans, investigations in the area of biotechnology will be a significant component of the life sciences research to be conducted on the International Space Station (ISS). They encompass work on cell science and studies of the use of microgravity to grow high-quality protein crystals. Both these subdisciplines are advancing rapidly in terrestrial laboratories, fueled by federal and industrial research budgets that dwarf those of NASA's life science program. Forging strong and fruitful connections between the space investigations and laboratory-bench biologists, a continual challenge for NASA' s life sciences program, is thus of great importance to ensuring the excellence of ISS research. This report evaluates the plan for NASA's biotechnology facility on the ISS and the scientific context that surrounds it, and makes recommendations on how the facility can be made more effective. In addition to questions about optimizing the instrumentation, the report addresses strategies for enhancing the scientific impact and improving the outreach to mainstream terrestrial biology. No major redirection of effort is called for, but collectively the specific, targeted changes recommended by the task group would have a major effect on the conduct of biotechnology research in space.
Keywords: Space and Aeronautics

Climate, Climatic Change, and Water Supply - National Research Council (The National Academies Press, 1977)
Keywords: Environment and Environmental Studies

ISC Security Design Criteria for New Federal Office Buildings and Major Modernization Projects: A Review and Commentary - National Research Council (The National Academies Press, 2003)
In November 1999, GSA and the U.S. Department of State convened a symposium to discuss the apparently conflicting objectives of security from terrorist attack and the design of public buildings in an open society. The symposium sponsors rejected the notion of rigid, prescriptive design approaches. The symposium concluded with a challenge to the design and security professions to craft aesthetically appealing architectural solutions that achieve balanced, performance-based approaches to both openness and security.In response to a request from the Office of the Chief Architect of the Public Buildings Service, the National Research Council (NRC) assembled a panel of independent experts, the Committee to Review the Security Design Criteria of the Interagency Security Committee. This committee was tasked to evaluate the ISC Security Design Criteria to determine whether particular provisions might be too prescriptive to allow a design professional "reasonable flexibility" in achieving desired security and physical protection objectives.
Keywords: Engineering and Technology; Conflict and Security Issues

Making the Soldier Decisive on Future Battlefields - National Research Council (The National Academies Press, 2013)
The U.S. military does not believe its soldiers, sailors, airmen, and marines should be engaged in combat with adversaries on a "level playing field." Our combat individuals enter engagements to win. To that end, the United States has used its technical prowess and industrial capability to develop decisive weapons that overmatch those of potential enemies. In its current engagement—what has been identified as an "era of persistent conflict"— the nation's most important weapon is the dismounted soldier operating in small units. Today's soldier must be prepared to contend with both regular and irregular adversaries. Results in Iraq and Afghanistan show that, while the U.S. soldier is a formidable fighter, the contemporary suite of equipment and support does not afford the same high degree of overmatch capability exhibited by large weapons platforms—yet it is the soldier who ultimately will play the decisive role in restoring stability. Making the Soldier Decisive on Future Battlefields establishes the technical requirements for overmatch capability for dismounted soldiers operating individually or in small units. It prescribes technological and organizational capabilities needed to make the dismounted soldier a decisive weapon in a changing, uncertain, and complex future environment and provides the Army with 15 recommendations on how to focus its efforts to enable the soldier and tactical small unit (TSU) to achieve overmatch.
Keywords: Conflict and Security Issues; Engineering and Technology